2020
DOI: 10.1055/a-1179-8326
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Performing Mental Exertion during Cycling Exercise on Fatigue Indices

Abstract: This study investigated the effect of performing prolonged mental exertion during submaximal cycling exercise on exercise tolerance and fatigue. Participants performed 5 experimental sessions. Session 1: determination of cycling peak power output. Sessions 2 and 3: cycling to exhaustion at 65% peak power output with mental exertion or watching a movie. Sessions 4 and 5: cycling for 45 min at 65% peak power outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 56 publications
(91 reference statements)
2
18
0
1
Order By: Relevance
“…It was hypothesized that self‐control exertion would lead to an increase in plasma cortisol concentration, given that combined physical and mental exertion has been shown to result in elevated cortisol. 39 However, there was no difference in cortisol between the self‐control exertion and control trials at any time point. Therefore, the present study provides preliminary evidence that cortisol is not an underpinning mechanism explaining the negative effects of self‐control exertion on subsequent sporting skill performance and sustained attention.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…It was hypothesized that self‐control exertion would lead to an increase in plasma cortisol concentration, given that combined physical and mental exertion has been shown to result in elevated cortisol. 39 However, there was no difference in cortisol between the self‐control exertion and control trials at any time point. Therefore, the present study provides preliminary evidence that cortisol is not an underpinning mechanism explaining the negative effects of self‐control exertion on subsequent sporting skill performance and sustained attention.…”
Section: Discussionmentioning
confidence: 85%
“…The present study is the first to examine the effects of self‐control exertion on plasma cortisol concentration. It was hypothesized that self‐control exertion would lead to an increase in plasma cortisol concentration, given that combined physical and mental exertion has been shown to result in elevated cortisol 39 . However, there was no difference in cortisol between the self‐control exertion and control trials at any time point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,31,35 The physiological measures, such as HR, lactate, and oxygen consumption during an endurance task exercise, seem to undergo no changes when subjects are mentally fatigued. 3,4,10 Smith et al 4 also no found difference for the HR throughout of a physical endurance task between mental fatigue and control experimental conditions in amateur soccer players. Specifically for cycling, Barzegarpoor et al 10 also no revealed difference for the HR throughout of various physical endurance tasks between mental fatigue and control conditions.…”
Section: Discussionmentioning
confidence: 94%
“…(2022) [ 1 ] n = 282 OFER ( α = 0,85) Chronische Fatigue (CF) und Erschöpfung werden hier synonym verwendet; CF/Erschöpfung wird oft als ein langwieriger Zustand betrachtet und beinhaltet körperliche, mentale und emotionale Elemente, inklusive anhaltender Müdigkeit, bei der die Genesung nie vollständig eintreten kann Barzegarpoor et al. (2020) [ 3 ] n = 10 Fatigue ist ein sehr komplexes Phänomen, das die menschliche Leistungsfähigkeit bei sportlichen Wettkämpfen und Aktivitäten des täglichen Lebens einschränkt Bauer et al. (2020) [ 4 ] n = 24 Fatigue ist ein physiologisches und psychologisches Phänomen, welches bei verschiedenen körperlichen Aktivitäten in unterschiedlichem Ausmaß auftritt.…”
Section: Methodikunclassified